Classification Email Spam using Naive Bayes Algorithm and Chi-Squared Feature Selection - Ningsih, Maylinna Rahayu; Unjung, Jumanto; Farih, Habib al; Muslim, Much Aziz ((JAIS) Journal of Applied Intelligent System, 2024)
Spam email is a problem that disturbs and harms the recipient. Machine learning is widely used in overcoming email spam because of its ability to classify emails into spam or non-spam. In this research, the Naïve Bayes algorithm is initiated with the Chi-Squared selection feature to classify spam emails. So that the implementation is able to increase accuracy for better performance in classification. The feature selection method is used to direct the model's attention to features that are related to the target variable. In this study, the chi squared feature uses a value of K = 2500, with an accuracy of 98.83% which shows an increase in model performance compared to previous research. So that the Naïve Bayes model with the Chi-Squared selection feature is proven to provide better performance.